1996
DOI: 10.1021/tx950117e
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation of PCBs to Quinones:  Reactivity toward Nitrogen and Sulfur Nucleophiles and Influence of Superoxide Dismutase

Abstract: Polychlorinated biphenyls (PCBs) may undergo cytochrome P-450-catalyzed hydroxylations to form chlorinated dihydroxybiphenyl metabolites. When the hydroxyl groups are ortho or para to each other, oxidation to a quinone may be catalyzed by peroxidases present within the cell. In order to study the reactivity of PCB-derived quinones, selected chlorophenyl 1,2- and 1,4-benzoquinones were synthesized and characterized, including their reduction potentials against a saturated calomel electrode. Two quinones, 4-(4'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 25 publications
1
165
1
Order By: Relevance
“…A similar reactivity profile has been observed for the benzoquinones of polychlorinated biphenyls (24). Reactions with nucleotides are even Reaction mixtures contained 100 μM PCP, 50 μM NADPH, and 50 μM NADH, except where indicated.…”
Section: Discussionsupporting
confidence: 69%
“…A similar reactivity profile has been observed for the benzoquinones of polychlorinated biphenyls (24). Reactions with nucleotides are even Reaction mixtures contained 100 μM PCP, 50 μM NADPH, and 50 μM NADH, except where indicated.…”
Section: Discussionsupporting
confidence: 69%
“…Marchlewicz et al (226) demonstrated that many spermatozoa of leadexposed rats had abnormal reactions of antioxidant enzymes in the midpiece, suggesting that impairment of free-radical scavenging enzymes may be an important factor in lead-induced ROS formation. Although no studies report oxidative stress in sperm following exposure to PCBs, the ortho-and para-hydroxylated metabolite of PCBs can be converted to quinones by peroxidases (227). The quinones can undergo redox cycling to produce ROS, and 8-OHdG is formed in an in vitro system of calf thymus DNA, lactoperoxidase, and 3,4-dichloro-2´,5´-dichlorobiphenyl (228).…”
Section: Oxidative Stress and Dna Damage In Spermmentioning
confidence: 99%
“…Arene oxides can undergo further biotransformation to a mono-hydroxylated form and further to di-hydroxylated metabolites, which may be oxidized to quinones (McLean et al, 1996a). The arene oxide and quinone metabolites are electrophiles and can bind to nucleophilic sites in amino acids, proteins, and DNA (Amaro et al, 1996;Arif et al, 2003;McLean et al, 1996b;Pereg et al, 2002;Pereg et al, 2001;Srinivasan et al, 2001;Srinivasan et al, 2002;Tampal et al, 2003). Also, during this oxidative metabolism reactive oxygen species (ROS) can be generated, which produce 8-oxo-dG and DNA strand breaks (McLean et al, 1998;Oakley et al, 1996;Srinivasan et al, 2001).…”
Section: Mutant Frequency and Mutations Caused By Pcb3 And 4-oh-pcb3mentioning
confidence: 99%